2015
DOI: 10.1186/s13322-015-0009-7
|View full text |Cite
|
Sign up to set email alerts
|

Autocatalytic sets in E. coli metabolism

Abstract: Background: A central unsolved problem in early evolution concerns self-organization towards higher complexity in chemical reaction networks. In theory, autocatalytic sets have useful properties to help model such transitions. Autocatalytic sets are chemical reaction systems in which molecules belonging to the set catalyze the synthesis of other members of the set. Given an external supply of starting molecules -the food set -and the conditions that (i) all reactions are catalyzed by at least one molecule, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
89
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 82 publications
1
89
0
Order By: Relevance
“…Indeed, cellular biochemistry seems to be rife with networked autocatalytic sets (Sousa et al 2015). The facility with which chains of nucleotides can be copied with tolerable accuracy, along with their offering a range of catalytic (Breaker et al, 2003) and regulatory (Breaker, 2012) possibilities, lends plausibility to RNA as a substrate for RAF set formation in the prebiotic world.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, cellular biochemistry seems to be rife with networked autocatalytic sets (Sousa et al 2015). The facility with which chains of nucleotides can be copied with tolerable accuracy, along with their offering a range of catalytic (Breaker et al, 2003) and regulatory (Breaker, 2012) possibilities, lends plausibility to RNA as a substrate for RAF set formation in the prebiotic world.…”
Section: Introductionmentioning
confidence: 99%
“…Modern cellular metabolism is enzyme-based, 67 but >60% of enzyme mechanisms described to date involve one or more cofactors (Ribeiro et 68 al., 2018) and 40% of all proteins crystallized have a bound metal relevant to their function 69 (Guengerich, 2016). RAFs can thus be identified in modern metabolism (Sousa et al, 2015) In search of RAFs, we investigated different levels of ancient metabolism preserved in 77 modern cells. Starting with the biosphere level of the KEGG database, we first removed all 78 eukaryote-specific reactions, and then peeled back one more layer of time by examining 79 anaerobic metabolism.…”
mentioning
confidence: 99%
“…They have been shown to exist in computational models of chemical reaction networks, as well as in real chemical and biological reaction networks (Hordijk & Steel, 2017). For example, Sousa et al (2015) showed that the metabolic network of E. coli forms a large autocatalytic (RAF) set, containing 98% of the reactions in that metabolic network. Assuming the same holds for most, if not all species, it seems a valid alternative to represent species by the RAF sets formed by their respective metabolic networks, as opposed to representing them by their genomes.…”
Section: Ecosystems and Autocatalytic Setsmentioning
confidence: 99%